Emotional Divorce and its Relationship with Psychological Stress among Married Nurses Working at Jordan University Hospital - Mohammad Alkhawaldeh; Yahya Alqatawneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aimed at dentifying the level of emotional divorce and its relationship with psychological stress among married nurses working at the University of Jordan Hospital. Methods: The study adopted the descriptive-relational approach; for its suitability to the nature of the study and its research purposes. The study sample consisted of (64) nurses. Tow Scales of Emotional Divorce, psychological Stress was developed and their psychometric properties were functionally appropriate when they were extracted. Results: The results showed that the level of emotional divorce, and the level of psychological stress for both were moderate. There was a positive correlation between emotional divorce and psychological stress. The results also showed that the level of emotional divorce and psychological stress did not differ based on gender, educational level and work experience. and finally, the results showed that the level of emotional divorce and psychological stress varies based on the duration of the marriage and in favor for category married couples who spent more than 10 years. Conclusions: The study encouraged hospital managements and related authorities on the necessity of directing the attention to the nurse's psychological aspect because of its impact on their performance, through counseling and training programs, and psychological support groups that help reduce and deal with psychological stress.